Mechatronics 2013 Recent Technological and Scientific Advances - Březina, Tomáš; Jabloński, Ryszard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Mechatronics, as the integrating framework of mechanical engineering, electrical engineering, computer technology, control engineering and automation forms a crucial part in the design, manufacture and maintenance of a wide range of engineering products and processes. The mechatronics itself changes rapidly in last decade, from original mixture of subfields into original approach in engineering as a technical discipline. The book you are holding is aimed to help the reader to orient in this evolving field of science and technology. „Mechatronics 2013: Recent Technological and Scientific Advances“ is the fourth volume following the previous editions in 2007, 2009 and 2011, providing the comprehensive and accessible coverage of advances in mechatronics presented on the 10th International Conference Mechatronics 2013, hosted this year at the Brno University of Technology, Czech Republic. The contributions, that passed the thorough review process, give an insight into current trends in research and development among Mechatronics 2013 contributing countries, with paper topics covering design and modeling of mechatronic systems, control and automation, signal processing, robotics and others, keeping in mind the innovation benefits of mechatronics design approach, leading to the development, production and daily use of machines and devices possessing a certain degree of computer based intelligence.
Design, Modeling and Simulation of Mechatronic systems -- Electrical Machines, Drives & Power Electronics -- Measurement and Diagnostics -- Robotics -- Control and Automation -- Biomedical and Biomechanical Engineering -- Mechatronic Education.
Keywords: Mechatronics; Robotics; Automation; Mechatronics; Robotics and Automation